FATWA MUI MELAWAN KORUPSI: ANALISIS SEJARAH EFEKTIFITAS FATWA MUI TENTANG HARAMNYA SUAP DAN KORUPSI DI AWAL ERA REFORMASI - Muhammad As'ad (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
It is indisputable that fatwa plays a significant role in the society. This is the case because fatwas played a considerable role in the growth and gradual change of Islamic substantive law. However, eventhough fatwa is an important part of religious authority, how one fatw? is effective in influencing people’s attitudes and behavior is being questioned. This article explains the extent to which Majelis Ulama Indonesia’s (MUI) fatwa could be effective in changing people’s attitude toward corruption. Especially in Indonesia which was known as one of the worst country Corruption Perception Index. This article is based on a qualitative research using content analysis by scrutinizing the the MUI fatwa on bribery, corruptions and present for government officials. The data for this research is taken from the montly magazine of MUI, Mimbar Ulama. This article argues that the MUI fatwa against corruption is not really effective in changing people’s behavior. This can be seen in Indonesian coruption index which was not really changing at least 5 years after the fatwa was enacted.